The Effect of Facilities and Service Quality on Consumer Satisfaction in Aqiqah Service Nurul Hayat Bojonegoro - Rahayuningsih, Eka (ITB AAS INDONESIA Surakarta, 2025)
This study discusses the influence of facilities and service quality on consumer satisfaction at Aqiqah Nurul Hayat Bojonegoro. This study aims to test whether there is a significant partial and simultaneous influence on consumer satisfaction at Aqiqah Nurul Hayat Bojonegoro. The type of research conducted is quantitative research with a population of Aqiqah Nurul Hayat Bojonegoro consumers, the sample size of the study was 30 respondents. The data collection technique in this study was by questionnaire, while the data analysis used multiple linear regression. From the test results, it can be concluded from the data analysis that there is a significant influence on facilities (X1) and service quality (X2) on consumer satisfaction (Y) based on the F test or simultaneous test, there is an influence of service quality on consumer satisfaction and there is no influence on service facilities on consumer satisfaction based on the t test or partial test. Based on the determination coefficient test (R2), it means that the facility and service quality variables have an influence on consumer satisfaction with a percentage value of 41%, while the remaining (100-41)% = 69%.